PEMBERDAYAAN KEWIRAUSAHAAN ALUMNI DAN MAHASISWA MELALUI PENGEMBANGAN PELAYANAN KEBIDANAN PADA PRENATAL YOGA - Esmianti, Farida Esmianti; Febrina, Lydia; Eka Sari, Wenny Indah Purnama (LPPM Universitas Al Muslim, 2024)
This community service activity was held on October 7 2022, in the form of a 1 day online workshop with a duration of 4 hours in the Campus B Auditorium. The formation of an entrepreneurial group for this activity went through the following stages: 1) socialization of PPK activities to students and alumni of the Curup District Midwifery Study Program. Rejang Lebong and Kepahiang, 2) tenant selection, 3) providing each group with management techniques in entrepreneurship, marketing techniques, financial techniques, as well as exploring and cultivating an entrepreneurial spirit, 4) training and mentoring in complementary therapies in midwifery, namely Prenatal Yoga Classy, ​​5) action plan by providing complementary midwifery services for pregnant and postpartum women, and 6) evaluation and monitoring. The results of this activity concluded that being an entrepreneur for graduates is not only focused on looking for work, but looking for ideas and innovations to open up new job opportunities for people in need, thereby improving the economy, marked by reduced unemployment. Forming and developing an entrepreneurial spirit for midwifery students and alumni requires assistance and strengthening efforts in complementary midwifery services, so that graduates can develop new innovative ideas, be independent, creative, disciplined and not give up easily in opening their own business in accordance with the business plan that has been designed. From this community service activity, efforts are made to form an entrepreneurial spirit, especially for students and alumni in complementary midwifery services.